Biodegradable Plastic from Klobot Waste with Glycerol as an Alternative to Conventional Plastic and Supports SDGs - Salmanera Senja Lopiani; Achmad Ali Fikri (CV. Generasi Intelektual Digital (GEN ID), 2024)
Organic waste, including corn husks, poses a significant environmental problem in Indonesia, particularly in food industry areas like the roasted corn kiosks at the Wergu Wetan Sports Hall, Kudus Regency. Currently, 33.57% of organic waste is left unmanaged, contributing to environmental pollution (National Waste Management Information System, 2024). Similarly, plastic waste is a pressing issue, with 5.4 million tons generated annually, causing severe environmental harm (Indonesia Solid Waste Association, 2024).This research focuses on creating bioplastics from corn husk waste as an eco-friendly alternative to conventional plastics. Using glycerol as a plasticizer and acetic acid to enhance strength, the study explored various formulations of husk, glycerol, and acetic acid to develop bioplastics with optimal physical characteristics. The findings indicate that acetic acid improves the transparency and strength of the material, while the glycerol ratio influences its flexibility and thickness. A formulation ratio of 5:2:1 (husk:glycerol:acetic acid) yielded the best results in physical property tests. Degradation tests further revealed that these bioplastics decompose quickly through natural biodegradation processes. The study demonstrates the potential of husk-based bioplastics as a sustainable alternative to reduce the environmental impact of plastic waste. With a suitability rate of 77.1% (Akbar and Sriwiyana, 2011), these bioplastics align with efforts to achieve Sustainable Development Goals (SDGs) in waste management and environmental preservation in Indonesia.